HUKUM ISLAM MASA KESULTANAN DELI: - Harahap, Radinal Mukhtar (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-undangan, dan Ekonomi Islam, 2020)
Islamic legal discourse on a practical level is often understood to be limited to the problem of istinb?t, fiqh or ushul fiqh. There is a challenge to expand it to include philosophy, normative and empirical cases. Study of manuscript is one of the related by that studies. This article presents Tanq?h al-Zun?n ?an Mas?'il al-Maim?n by Shaykh Hasan Maksum as an identifier of the political and social links to Islamic legal in the Deli Sultanate. From this it was found that the sultanate had a stake in the determination of the law as well as the role of the ulama in maintaining the attitude as a speaker of legal provisions. There are seven legal issues that are discussed normatively, and they originate from the existence of arguments in the community. This manuscript not just addition Islamic legal in the Deli Sultanate, it also showed the authority of Shaykh Hasan Maksum as a 'brilliant star' scholar in legal matters, although it was rarely discussed and raised at the research level.